Coating material of air sealing in coal mine: Clay composite slurry (CCS) - Zhou, F.; Shi, B.; Liu, Y.; Song, X.; Cheng, Jianwei; Hu, S. (2013)
Coating technology is commonly utilized for the air leakage prevention in the roadway of coal mines in China because of low work load and high efficiency. However, traditional coating materials (e.g. concrete) and chemical materials (e.g. polyurethane foam) utilized for air leakage prevention and underground fire, are impracticable to be broadly utilized because of their difficult appliance, high transportation cost and high prices. In terms of the characteristics of underground coating technology, specific requirements for coating air-sealing materials were put forward. The optimized mixing ratio for clay composite slurry (CCS) based on clay, cement, additives (sodium silicate) and glass fibers was determined. The incombustibility of the material was verified using a self-made box test system. The micropore structure of the materials was determined with a micropore structure analyzer. The CCS coating material produced has excellent air sealing performance and very good fire resistance, air tightness, low dehydration, and crack prevention after coagulation in addition to the low cost. Moreover, it has very good application prospects for coating along gob-side roadways, sealed-wall and permanent maintenance roadway, etc. © 2013 Elsevier B.V.